2016
DOI: 10.1139/cjps-2015-0268
|View full text |Cite
|
Sign up to set email alerts
|

Response of cool-season grain legumes to waterlogging at flowering

Abstract: Soil flooding and submergence, collectively termed waterlogging, are major abiotic stresses that severely constrain crop growth and productivity in many regions. Cool-season grain legumes can be exposed to submersion both at the vegetative and reproductive stages. Limited research has been carried out on these crops with waterlogging imposed at flowering. We evaluated how waterlogging periods of 0, 5, 10, 15, and 20 d at flowering affected seed yield, biomass of shoots, roots and nodules, and N uptake of faba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 24 publications
5
32
0
Order By: Relevance
“…The sensitivity of field pea to waterlogging is further highlighted by the detrimental effect on plant seed production, with values of 4 and 8% of controls for early- and late-waterlogging. Even waterlogging for 5 days at the beginning of flowering decreased seed production in field pea to 38% of controls (Pampana et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of field pea to waterlogging is further highlighted by the detrimental effect on plant seed production, with values of 4 and 8% of controls for early- and late-waterlogging. Even waterlogging for 5 days at the beginning of flowering decreased seed production in field pea to 38% of controls (Pampana et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Only some studies have analyzed the impact of waterlogging throughout the entire plant life-cycle, describing responses in vegetative growth and seed production. As examples: in wheat, 20 days of waterlogging on 3–4 leaf-stage plants resulted in a final dry mass and yield representing 95 and 90% of controls, respectively (Collaku and Harrison, 2002; Pampana et al, 2016a); in barley, plants attained 85 and 90% of controls in dry mass and yield when waterlogged for 20 days at 3–4 leaf-stage (Masoni et al, 2016); in rapeseed, 21 days of soil hypoxia, applied to 5-leaf stage plants, constrained growth as the stressed individuals attained 77% in dry mass and 73% in yield compared to the control (Leul and Zhou, 1998); in field pea, 5 days of waterlogging had a substantial impact on plant dry mass accumulation and seed production as, respectively, stressed plants attained 35–50% and 5–25% of controls (Jackson, 1979; Pampana et al, 2016b). Nevertheless, information on root and shoot growth rates during waterlogging and subsequent recovery is scarce, and studies to functionally link leaf physiological responses with growth (i.e., RGR) and seed production (but see Li et al, 2011 for wheat are few).…”
Section: Introductionmentioning
confidence: 99%
“…As in early waterlogging, the root system was greatly affected by the end of the treatment, as a result of generalised root decay, and with no ability to recover by maturity. In this regard, Pampana et al (2016) observed that plants only reached 33% of controls in root length, and Cannell et al (1979) registered a root dry mass of 20% of controls at maturity.…”
Section: Field Peamentioning
confidence: 93%
“…This constitutes a major threat to regional crop production. Pea is very prone to WL, even more than other grain legumes (Solaiman et al, 2007; Pampana et al, 2016). In recent years, unseasonal rain during sowing exposed the pea crop to WL stress (Zaman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%